2022
DOI: 10.1038/s42003-022-03784-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term microglial phase-specific dynamics during single vessel occlusion and recanalization

Abstract: Vascular occlusion leading to brain dysfunctions is usually considered evoking microglia-induced inflammation response. However, it remains unclear how microglia interact with blood vessels in the development of vascular occlusion-related brain disorders. Here, we illuminate long-term spatiotemporal dynamics of microglia during single vessel occlusion and recanalization. Microglia display remarkable response characteristics in different phases, including acute reaction, rapid diffusion, transition and chronic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Interestingly, the so-called repair-associated microglia were recently described in a cerebrovascular injury model as microglia with proangiogenic properties, expressing high levels of VEGF and concomitant physiological microglial levels of P2RY12 and CX3CR1 [34]. Using the laser ablation technique for single vessel occlusion, Xie et al demonstrated that retraction and elongation of microglial processes in the first hours, as a rapid response and slower migration of cell somata toward the occlusion site, were temporally dependent on the spatial distance of microglia from the occluded vessel [35]. In a model of permanent middle cerebral artery occlusion (MCAo), amoeboid microglia were shown to be present in the border area of the infarct lesion as early as 30 minutes after occlusion (Fig.…”
Section: Microgliamentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the so-called repair-associated microglia were recently described in a cerebrovascular injury model as microglia with proangiogenic properties, expressing high levels of VEGF and concomitant physiological microglial levels of P2RY12 and CX3CR1 [34]. Using the laser ablation technique for single vessel occlusion, Xie et al demonstrated that retraction and elongation of microglial processes in the first hours, as a rapid response and slower migration of cell somata toward the occlusion site, were temporally dependent on the spatial distance of microglia from the occluded vessel [35]. In a model of permanent middle cerebral artery occlusion (MCAo), amoeboid microglia were shown to be present in the border area of the infarct lesion as early as 30 minutes after occlusion (Fig.…”
Section: Microgliamentioning
confidence: 99%
“…Using the laser ablation technique for single vessel occlusion, Xie et al. demonstrated that retraction and elongation of microglial processes in the first hours, as a rapid response and slower migration of cell somata toward the occlusion site, were temporally dependent on the spatial distance of microglia from the occluded vessel [35]. In a model of permanent middle cerebral artery occlusion (MCAo), amoeboid microglia were shown to be present in the border area of the infarct lesion as early as 30 minutes after occlusion (Fig.…”
Section: Local Macrophage Respondersmentioning
confidence: 99%